Menyama Braya dalam Masyarakat Bali (Perspektif Pendidikan Agama Hindu) - Sukariawan, Putu (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2024)
Hindu religious education must be taught to become a guide to life that contains many values ​​and norms that will help people live in all things, including their relationship with Sang Hyang Widhi, fellow humans, and their environment. Menyama braya, meaning